Developing Warrants for Designing Continuous Flow Intersection. (29th May 2022) - Almoshaogeh, Meshal; Abou-Senna, Hatem; Radwan, Essam; Kamal, Tarek Lotfy; Alharbi, Fawaz; Alfawzan, Mohammed; Haider, Husnain
Abstract : The increase in the left-turn demand is the main cause of congestion at conventional intersections, and the traditional countermeasures are inadequate to solve this congestion due to the high changes in demand. This paper looks at the justifying threshold to redesign a signalized intersection from a conventional intersection (CI) to a continuous flow intersection (CFI) and create performance guidelines for decision-makers and professionals deciding to consider the alternative. A performance comparison between the CI and CFI was conducted to define the main parameters affecting the operational performance. To accomplish the paper's objective, candidate locations that have already implemented the CFI were identified, and the location with sufficient data for analysis was selected. After the consideration of different evaluation tools, microsimulation (VISSIM 8) was utilized to model the before and after conditions of the location. Using the field data, signal optimization and driving behavior parameter sensitivity analysis were performed to calibrate the models to replicate real-life conditions. Afterwards, an experiment was designed to examine the different factors that affect the efficiency of each design. The experiment involved 72 different configurations of CFI and CI with 5 different volume levels and used two measures of effectiveness, average vehicle delay, and capacity to assess the results. The results were used to develop guidelines that will help the decision-makers to decide which design should be considered, which will result in developing a decision support system that will accelerate finding which design is superior to others.